2007
DOI: 10.1210/en.2006-1371
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Blockade of Nitric Oxide Synthesis Reduces Adiposity and Improves Insulin Resistance in High Fat-Induced Obese Mice

Abstract: Genetic deletion of inducible nitric oxide synthase (NOS) in mice has been shown to improve high-fat diet (HFD)-induced insulin resistance. However, a pathophysiological role of endogenous nitric oxide (NO) in obesity-related insulin resistance remains controversial. To address this issue, we examined the metabolic phenotypes in HFD-induced obese mice with chronic blockade of NO synthesis by a NOS inhibitor, N(G)-nitro-l-arginine methyl ester (L-NAME). Six-week-old male C57BL/6j mice were provided free access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 42 publications
4
61
0
1
Order By: Relevance
“…Eleven studies show no effect, and 9 even report a decrease. The variance of reported effect sizes tends to be higher on the mRNA level and in some cases is divergent from protein levels even in the same samples (75).…”
Section: Methodological Levelmentioning
confidence: 90%
“…Eleven studies show no effect, and 9 even report a decrease. The variance of reported effect sizes tends to be higher on the mRNA level and in some cases is divergent from protein levels even in the same samples (75).…”
Section: Methodological Levelmentioning
confidence: 90%
“…Furthermore, high-fat-fed obese mice show an increased level of iNOS and the absence of the iNOS gene protects against high-fat diet-induced skeletal muscle insulin resistance (13). Blockade of iNOS by N G -nitro-L-arginine methyl ester (L-NAME) improves high-fat diet-induced obesity and glucose intolerance in experimental rodents (23). The present data also demonstrated that lack of the iNOS gene also prevented lipid infusion-induced insulin resistance in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…After 12 weeks of either a standard diet (SD) or a HF diet, alone or combined with L-NAME (100 mg/kg/d), it was found that L-NAME treatment significantly attenuated body-weight gain in both groups of mice without affecting calorie intake. Chronic NOS blockade by L-NAME in mice ameliorated HF diet induced adiposity and glucose intolerance; it also reduced adipose inflammation and improved insulin signalling in skeletal muscle [26].…”
Section: Discussionmentioning
confidence: 96%